Development of an Encyclopedia Based on the Integration of Islam and Science to Improve Understanding of the Motion System in Humans for Grade V Students of SDIT Al-Irsyad Pamekasan - A’yun Sufyan, Qurrotul; Wahidmurni, Wahidmurni; Astuti, Rini Nafsiati (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
Encyclopedia teaching materials can enhance the learning process by being clearly and attractively packaged, which helps prevent boredom and engages both students and teachers. This is particularly beneficial for grade V science teachers at SDIT Al-Irsyad Pamekasan, who have observed that many students' achievements fall below the KKM (Minimum Completeness Criteria). By integrating Islam and science into these encyclopedia teaching materials, teachers can better support students' understanding of human motion systems and strengthen their confidence in Allah SWT. This research aims to evaluate (1) the feasibility and (2) the effectiveness of these integrated encyclopedia materials at SDIT Al-Irsyad Pamekasan. Using the Research and Development (R&D) approach with the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation, the study involved fifth-grade students as subjects. Results indicate that the encyclopedia is highly valid, effective, and attractive, meeting user needs. Validation results show that material experts rated the encyclopedia at 96%, design experts at 87.5%, language validation at 80%, and science learning experts at 92%, all in the